The Role and Influence of the Tourism Industry of the Crimean Region on Economic Development - D. G. Shсhipanova; D. D. Burkaltseva; E. U. Osmanova; A. A. Yanovskayav (Модернизация, инновация, развитие, 2017)
Purpose: the aim of the article is the role and influence of tourism on the development of the economy at all levels of the economic system (example: Republic of Crimea). The article considers the methodology for analyzing the indices of social and economic growth in the branch of the Republic of Crimea. The role and influence of tourism on the economy is considered. Tasks of the article: analysis of the works of foreign and domestic scientists on the role and influence of tourism on the development of the economy; to conduct an analysis of the sectoral structure of the gross value added of the Russian Federation; describe the growth of socio-economic indicators; identify the stages of the methodology for analyzing the indicators of the social and economic growth of the tourist industry; to give an analysis of indicators characterizing the socioeconomic growth of the tourist industry of the Republic of Crimea; construct the dependence of the amount of declared amounts of investment projects on the number of tourists who visited the Republic of Crimea. Methods: the dialectical method of scientific cognition was applied in studying the role and influence of tourism on the development of the economy, calculation and analytical methods for monitoring, measuring, analyzing and comparing indicators that characterize the social and economic growth of the tourist industry of the Republic of Crimea. Results: in modern conditions, the development of the tourism sector, as a source of sustainable development of the state economy, acquires priority development. The tourism industry has a huge impact on the economy of the region, being the locomotive of the development of many other branches of management and providing non-raw budget receipts. The analysis of the works of foreign and domestic scientists makes it possible to talk about the integrated mechanism of the role and influence of tourism on the development of the economy at all levels of the economic system and, in general, the national economy of the country. Its essence is as follows: the gradual increase in the socio-economic standard of living of the country's population increases its needs for rest and leisure, which increases domestic and outbound tourist flows. The coefficient of determination R² = 0.0191 showed that 1.91% of the variation of the "declared amount of investment projects, applications" is due to the variation in the sign "the number of tourists who visited the Republic of Crimea", and 98.09% of the variation is already associated with the impact of other factors not taken into account. Conclusions and Relevance: the spread of tourism is becoming a stimulating factor for the development of the tourism services sector: the tourism industry is growing in the budget, the number of employees in the tourism sector is growing. Increased investment in the tourism sector leads to the creation of tourist facilities and the development of tourism infrastructure, increases the attractiveness of the national sector of tourism services. This stimulates the growth of domestic and incoming tourist flows and ensures an increase in the country's socio-economic development. The social and economic growth of the sector as a whole is promoted by institutional support, developed state regulatory and legal regulation in the sphere of tourism, interaction of public-private partnerships, staffing, diversification of tourism products through the development of various types of tourism, thereby eliminating the reason for the seasonality of tourism enterprises and increasing income.